Clinical impact of chronic substance abuse in a Norwegian ICU‐population. Issue 4 (29th December 2020) - Tollisen, K. H.; Hadley, C. L.; Bjerva, M.; Dahl, G. T.; Högvall, L. M.; Sandvik, L.; Andersen, G. Ø.; Heyerdahl, F.; Jacobsen, D.
Abstract: Background: The clinical impact of chronic substance abuse of alcohol and drugs—referred to as substance use disorders (SUD)—is often overlooked in the intensive care (ICU) setting. The aims of the present study were to identify patients with SUD—regardless of cause of admission—in a mixed Norwegian ICU‐population, and to compare patients with and without SUD with regard to clinical characteristics and mortality. Methods: Cross‐sectional prospective study of a mixed medical and surgical ICU‐population aged ≥18 years in Oslo, Norway. Data were collected consecutively, using a questionnaire including the AUDIT‐C test, medical records and toxicology results. Patients classified with SUD were divided into the subgroups alcohol use disorders (AUD) and drug use disorders (DUD). Results: Overall, 222 (26%) of the 861 patients included were classified with SUD; 137 (16%) with AUD and 85 (10%) with DUD. 130/222 (59%) of the SUD‐patients had substance abuse‐related cause of ICU‐admission. Compared to non‐SUD patients, DUD‐patients were younger (median age 42 vs 65 years) and had lower SAPS II scores (41 vs 46), while AUD‐patients had higher SOFA scores (8.0 vs 7.3). Overall, age‐adjusted logistic regression analysis showed similar hospital mortality for SUD‐patients and non‐SUD patients, but AUD was associated with increased mortality among medical patients and in patients with sepsis (OR 1.7 (95% CI 1.0‐2.8), and OR 2.6 (95% CI 1.1‐6.2)). Conclusion: One in four ICU‐patients had SUD regardless of cause of admission. Alcohol use disorder was associated with increased mortality in medical patients and in patients with sepsis.